1983
DOI: 10.1149/1.2119507
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating of Cyclic Multilayered Alloy (CMA) Coatings

Abstract: A new technique has been developed for producing laminated composites of cyclic multilayered alloy (CMA) electrodeposits. The thickness and composition of the individual layers of the CMA deposits are altered precisely and conveniently by cyclic modulation of the cathodic current or potential during electrodeposition. It is thus possible to modify the structure to obtain laminated composite coatings which may have desirable engineering properties. Wear and corrosion resistances, mechanical hardness and strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 13 publications
0
54
0
1
Order By: Relevance
“…Deposition of such structures was first demonstrated by Brenner [4], while Cohen et al [97] obtained an Ag-Pd alloy with periodically changing composition by alternating the current density, and such structure showed improved wear performance of electrical contacts. In order to obtain laminar metal structure with the thickness of individual layers (with the second layer being Cu-Ni alloy with small amount of Ni) of 300 nm in the system Cu-Ni, pulsating regimes were used [98,99].…”
Section: Formation Of Laminar Deposits By Pulsating Current Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition of such structures was first demonstrated by Brenner [4], while Cohen et al [97] obtained an Ag-Pd alloy with periodically changing composition by alternating the current density, and such structure showed improved wear performance of electrical contacts. In order to obtain laminar metal structure with the thickness of individual layers (with the second layer being Cu-Ni alloy with small amount of Ni) of 300 nm in the system Cu-Ni, pulsating regimes were used [98,99].…”
Section: Formation Of Laminar Deposits By Pulsating Current Regimesmentioning
confidence: 99%
“…It was shown that such structures possessed higher tensile strength [98] and microhardness [99]. In the application of pulsating regimes [97][98][99] three types of pulses, schematically presented in Fig. 1.36, were used.…”
Section: Formation Of Laminar Deposits By Pulsating Current Regimesmentioning
confidence: 99%
“…For example, it has been observed that silver/palladium multilayers can still maintain layer planarity in spite of small disruptions (compared to diffusion layer thickness) in the electrodeposit, resulting from the incorporation of inclusions (Cohen 1983). However, larger disruptions may be amplified as growth is favoured in the surrounding areas of an inclusion site (Cohen 1983). Consequently, surface roughness increases as deposition continues and planarity may be lost.…”
Section: Microstructure Of Multilayered Materialsmentioning
confidence: 99%
“…Even multilayered or compositionally modulated alloys (e.g. Cu-Pb [16], Cu-Ni [17,18], Ag-Pd [19], Ni-P [20]), metal matrix composites (e.g. Ni-SiC [3]), ceramics (e.g.…”
Section: Synthesismentioning
confidence: 99%